Engineering Mechanics: Statics & Dynamics - Khachane (Jivan); Shrivastava (Ruchi) ("4821, Parvana Bhawan,1st Floor, 24, Ansari Road,Delhi,New Delhi,India", 2006)
Engineering Mechanics
22.5
Keywords: Engineering Mechanics